A review of Islamic stock market, growth and real-estate finance literature - Hassan, M. Kabir; Aliyu, Sirajo; Saiti, Buerhan; Abdul Halim, Zairihan; Uluyol, Burhan (Emerald Group Publishing Ltd, 2019)
Purpose This paper reviews economic and finance research on Islamic investments. In the course of our review, we focus on the following issues: the performance of Islamic stock indexes, Islamic finance-growth nexus and Islamic real-estate investment trust market. Design/methodology/approach This literature survey consists of two stages such as random and systematic. It begins with a random search of articles with the intention to explore the three different areas of Islamic banking and finance. In order to maintain some level of quality of the literature review, we explored inside citations of articles based on relevant and recent articles from SCOPUS and Web of Science. Findings This paper represents an attempt to organise current research on Islamic stock markets, Islamic finance-growth nexus and Islamic real-estate finance: (1) the first prevailing finding is that Islamic stock indices are less volatile than conventional stock indices; (2) most empirical studies regarding Islamic finance-growth nexus focus on the impacts of banking sectors on growth and neglect other segments of the Islamic financial market; (3) based on our review of existing studies, there is no unanimous model for Islamic home financing in Islamic banks. Practical implications The mixed findings in this area hinder the understanding of Islamic investment and prevent identifying trends that support decision-making. Our review provides suggestions for prospective research directions. Most empirical studies regarding Islamic finance-growth nexus focus on the impacts of banking sectors on growth and neglect other segments of the Islamic financial market. Originality/value There is no literature review on Islamic finance-growth nexus and Islamic real-estate literature. Therefore, we are going to fill this gap to review these three different aspects of Islamic banking and finance.
WOS:000547823000001
Keywords: Islamic finance; Islamic investment; Islamic mutual fund; Stock market; Real-estate; G11; G10; R31